Principal–agent problems in multi-unit developments: The impact of developer actions on the on-going management of strata titled properties. (September 2016) - Easthope, Hazel; Randolph, Bill
This paper demonstrates the impact the actions of developers during the design and build phases of multi-unit residential developments can have on the quality and effectiveness of the on-going management of developments. The findings presented are drawn from a large research project that included interviews and surveys with property owners, executive committee (body corporate) members, strata (property) managers, and peak body representatives about the management of strata schemes in the state of New South Wales in Australia. A total of 1550 people were consulted. The actions of developers in the set-up of multi-unit developments (including build quality, design, allocation of unit entitlements, and levy setting) can have an important impact on the quality of buildings, the financial viability of schemes in the short-to-medium term, the balance of power between owners, the effectiveness of management and the nature and incidence of disputes. The paper concludes with a discussion of opportunities for integrating long-term management considerations into decision-making in the design and build phase to ensure management costs and costs to those using the property are minimized. The research will be of interest to those involved with property developments in international jurisdictions that have similar multi-unit ownership and management structures and in jurisdictions considering the introduction of similar forms of multi-unit ownership.